The DNA unwinding element: a novel, cis-acting component that facilitates opening of the Escherichia coli replication origin. - Kowalski, D (1989)
We have discovered that DNA supercoiling, in the absence of replication proteins, induces localized unwinding in the Escherichia coli replication origin (oriC) at the same sequence opened by the dnaA initiator protein. The DNA helix at the tandemly repeated, 13mer sequence is thermodynamically unstable, as evidenced by hypersensitivity to single-strand-specific nuclease in a negatively supercoiled plasmid, and demonstrated by stable DNA unwinding seen after two-dimensional gel electrophoresis of topoisomers. A replication-defective oriC mutant lacking the leftmost 13mer shows no nuclease hypersensitivity in two remaining 13mers and no detectable DNA unwinding on two-dimensional gels. The replication defect in the oriC mutant can be corrected by inserting a dissimilar DNA sequence with reduced helical stability in place of the leftmost 13mer. Thus, the helical instability of the leftmost 13mer, not the specific 13mer sequence, is essential for origin function. The rightmost 13mer exhibits helical instability but differs from the leftmost 13mer in its strict sequence conservation among related bacterial origins. The repeated 13mer region appears to serve two overlapping functions: protein recognition and helical instability. We propose that the cis-acting sequence whose helical instability is required for origin function be called the DNA unwinding element (DUE).